A monitoring and evaluation system in a research organization : a case of African Population and Health Research Center - Kiliswa, Matthew Shahi (Strathmore University, 2011)
The African Population and Health Research Center (APHRC) has gone through rapid expansion in terms of research focus, geographical scope, budget, staff and funders over the last 10 years. As a result, it became necessary to have an automated monitoring and evaluation (M&E) system to capture, monitor, and measure results as well as the impact of the Center’s work. Furthermore, an external review on the Center’s operations done in 2009 identified the need for a better projects and results tracking system and mechanism. Therefore, the development of the system is a significant milestone in the results based management of programs at APHRC. Initially, the system was to be out-sourced. However, after an assessment of six external Project Management Systems, the Center concluded that none was context specific to her needs as a research organization. It was also going to be expensive to procure and pay annual maintenance charges for the selected system. With the support of a core team composed of the System Developer, M&E Officer, Development Manager and Head of Finance and Administration, APHRC made the decision to develop an in-house system. The modules in the new automated M&E system are informed by the logic model and metrics in the Center’s M&E framework. The seven modules include: Grants, Project Progress Tracking and Reporting, Publications, Media Appearances, Policy Engagement Events and Outcomes, Training and Institutional Support, and Alumni Tracking. Open source software such as APACHE HTTP server, PHP, MySQL and other web design scripting languages such as Cascading Style Sheets (CSS) and Java Script have been used to design the system. The system is now in use at APHRC. The system can be accessed via the center’s Intranet.
Partial fulfillment to the requirements of the award of Master of Science in Computer Based Information Systems (MSCIS)
Keywords: Monitoring and Evaluation; ICT; African Population and Health Research Center